ANALISIS SISTEM DAN PROSEDUR PENYELESAIAN KLAIM ASURANSI JIWA PADA AJB BUMIPUTERA 1912 KANTOR WILAYAH MEDAN - Siska Permata Sari Harahap; Aqwa Naser Daulay (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to analyze the system and procedures for settling life insurance claims at the Medan Regional Office of Ajb Bumiputera 1912. The research method employed is descriptive research with a qualitative approach. Data were collected through in-depth interviews, observations, and document studies. The analysis results indicate that the system and procedures for settling life insurance claims at Ajb Bumiputera 1912, Medan Regional Office, have been well-designed to ensure effective and efficient services to customers. The procedures include stages of claim submission, verification, evaluation, and claim settlement. These findings illustrate the company's commitment to providing excellent service to customers and reaffirm the public's trust in the insurance institution. In conclusion, the existing system and procedures have yielded satisfactory results in settling life insurance claims, but they need continual improvement in line with technological advancements and customer needs.